2019
DOI: 10.1021/acs.jpca.9b02084
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insight into a Nonadiabatic Proton-Coupled Electron Transfer Mechanism of Reduced Flavin Oxygenation

Abstract: The oxygenation of reduced flavin has been a fascinating research hotspot in flavin-dependent proteins because it plays an indispensable role in cellular metabolism and has potential applications in biocatalysis. This spin-forbidden reaction of high efficiency is far from being fully understood. Although investigation on the flavin chemistry has been going on for more than 60 years, there are few mechanistic explanations for the reaction of the singlet-reduced flavin with triplet oxygen. In this paper, the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Moreover, ORR by most flavoenzymes studied in the past are conformed to undergo the initial single ET (ET-PT), , though the positive environment near the active site of enzymes can greatly accelerate the reaction rate . In contrast to that, recent theoretical research suggested that the initial single ET is coupled with a proton transfer for several specific flavoenzymes (CPET). Our work discloses that organic hydrides are potential reagents for O 2 reduction via MS-CPET. In addition, Thorpe et al argued that the solvation and the local polarity within the active site of flavoproteins could affect O 2 reactivity, which is consistent with our experimental results observed.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, ORR by most flavoenzymes studied in the past are conformed to undergo the initial single ET (ET-PT), , though the positive environment near the active site of enzymes can greatly accelerate the reaction rate . In contrast to that, recent theoretical research suggested that the initial single ET is coupled with a proton transfer for several specific flavoenzymes (CPET). Our work discloses that organic hydrides are potential reagents for O 2 reduction via MS-CPET. In addition, Thorpe et al argued that the solvation and the local polarity within the active site of flavoproteins could affect O 2 reactivity, which is consistent with our experimental results observed.…”
Section: Resultsmentioning
confidence: 88%
“…Hence, INT - L 4– and 3 O 2 form RC on the T 1 -PES, then via an intersystem crossing (ISC) to generate INT1 . Although the current computational method is not able to optimize the ISC structure and multireference methods cannot handle such large system, similar ISC processes have been investigated and validated in simpler systems as well. Following the formation of INT1 , geminal diol INT2 is produced via TS3 by nucleophilic attack, overcoming a low barrier of 1.9 kcal•mol –1 . Subsequently, INT2 is expected to transform into D 4– via TS4A .…”
Section: Resultsmentioning
confidence: 99%
“…In biological systems, metal-free flavindependent enzymes, molecular oxygen activation consists in electron transfer to O 2 from a closed-shell reduced flavin anion, chemisorption prior to charge transfer being clearly spin forbidden. [55] Quantum chemical modelling [56,57] further shows that coupled proton and electron transfer (CPET) is an important factor in making these transformations possible.…”
Section: Modelling Orr At Pedotmentioning
confidence: 99%